Teaching-Material Design Center: An ontology-based system for customizing reusable e-materials - Wang, Hei-Chia; Hsu, Chien-Wei (Computers & Education, 2006)
Use of electronic teaching materials (e-material) to support teaching is a trend. e-Material design is therefore an important issue. Currently, most e-material providers offer a package of solutions for different purposes. However, not all teachers and learners need everything from a single package. A preferable alternative is to find useful material from different packages and combine them for a particular course. Currently, most educators collect the material manually, which is time-consuming and may result in missed material. In this paper, we describe a system – the Teaching-Material Design Center, which follows the standard of Sharable Content Object Reference Model – to separate e-material for use as teaching templates and learning objects and to label the material with use of semantic metadata for searching. This system can find existing teaching templates and learning objects for e-material designers and provide a convenient environment for constructing customized e-material for different requirements. We describe the implementation and evaluation of the proposed system for a course. Our system is efficient in finding teaching templates and learning objects and shortening the e-material development process.
Keywords: Authoring tools and methods; Course template; E-material; Learning object semantic metadata; SCORM